A Sufistic Interpretation in Letto’s Songs: Exploring the Relationship between Humans and God through Religious, Philosophical, and Spiritual Elements - Fitria, Tira Nur (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
This research describes the Sufism and spiritual interpretation of several Letto Songs. This research uses descriptive qualitative. The analysis shows that religious meanings may be detected in the lyrics of Letto's song entitled “Sebelum Cahaya, Sandaran Hati, Ruang Rindu, Permintaan Hati, Lubang di Hati, Dalam Duka, Sebenarnya Cinta, Jalan Yang Hilang”. Overall, the religious sentiments contained in the Letto band's songs demonstrate that the words in Letto's songs may be utilized as reflection material or guidance for the general audience to better comprehend the religion. The meaning of Letto's song lyrics penetrates deep and sublime love, they make up the lyrics as if they were only conveyed to humans. Letto’s songs usually also tell stories about spirituality or contain religious values that are very strong in their song. If we understand Letto's songs, we must go through two understandings of text and non-text (meaning hidden behind the depths of words). If we only understand it from a textual point of view, we will only find Letto's songs are just love songs between a pair of humans. However, if we dissect the non-textual side, we will find a Sufistic understanding that songs are a reflection of the animosity between man and his Beloved; Lord. If we are more careful and absorb the lyrics of some of Letto's songs, we will surely feel as if we are being transported to a situation wherein in that space there are only us and God. In the Sufi world, the lyrics and stanzas of a song are a form of expression of love for God the Creator.